NK Cell Reconstitution After Autologous Hematopoietic Stem Cell Transplantation: Association Between NK Cell Maturation Stage and Outcome in Multiple Myeloma - Orrantia, Ane; Terrén, Iñigo; Astarloa-Pando, Gabirel; González, Carmen; Uranga, Alasne; Mateos-Mazón, Juan J.; García-Ruiz, Juan C.; Riñón, Marta; Rey, Mercedes; Pérez-Fernandez, Silvia; Zenarruzabeitia, Olatz; Borrego, Francisco (Frontiers in Immunology, 2021)
Autologous hematopoietic stem cell transplantation (autoHSCT) is a standard of care for transplant-eligible patients with multiple myeloma (MM). Among factors that influence outcome after autoHSCT, it has been suggested that the number of natural killer (NK) cells plays an important role. However, the impact that different NK cell subsets and their phenotype could have in disease progression after autoHSCT are less clear. For this reason, we have phenotypically and functionally characterized NK cells during immune system reconstitution after autoHSCT in 54 MM patients. Shortly after leukocyte recovery, an extensive redistribution of NK cell subsets occurs in these patients. In addition, NK cells undergo a profound phenotypic change characterized, among others, by their increased proliferative capacity and immature phenotype. Importantly, MM patients who showed lower frequencies of the mature highly differentiated NKG2A-CD57+ NK cell subset at +30 and +100 days after autoHSCT experienced superior progression-free survival and had a longer time to the next treatment than those with higher frequencies. Our results provide significant insights into NK cell reconstitution after autoHSCT and suggest that the degree of NK cell maturation after autoHSCT affects the clinical outcome of MM patients treated with this therapeutic strategy.